2018
DOI: 10.3892/ijmm.2018.3399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of midkine on gemcitabine resistance in biliary tract cancer

Abstract: Gemcitabine-based chemotherapy is one of the most effective and commonly used chemotherapeutic regimens for biliary tract cancer (BTC). However, development of resistance to this drug limits its efficacy. The present study aimed to explore the effects of midkine (MDK) on the resistance of BTC cells to gemcitabine. Cell viability and proliferation were measured by a Cell Counting Kit-8 assay and 5-ethynyl-2′-deoxyuridine staining, respectively. Western blot analysis was used to detect the expression of E-cadher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Moreover, MK engenders a cross-talk between the Notch signaling and JAK2/STAT3 signaling by inducing an interaction between the JAK2/STAT3 complex and Hes1, which is the downstream target of Notch-2 [51,53]. Recent studies have demonstrated that induced MK is significantly associated with chemoresistance in pancreatic cancer via the activation of NF-κB signaling and Hes1-induced JAK2/STAT3 signaling through cleavage and activation of MK-mediated Notch signaling [54,55]. Intriguingly, the binding of estradiol (E2) to ERβ results in the activated ER-β binding to the estrogen response element within the MK promoter, thereby leading to the induction of MK transcription, which enhances the EMT [56].…”
Section: Critical Modulators Of the Jak2/stat3 Signaling Pathway In Emtmentioning
confidence: 99%
“…Moreover, MK engenders a cross-talk between the Notch signaling and JAK2/STAT3 signaling by inducing an interaction between the JAK2/STAT3 complex and Hes1, which is the downstream target of Notch-2 [51,53]. Recent studies have demonstrated that induced MK is significantly associated with chemoresistance in pancreatic cancer via the activation of NF-κB signaling and Hes1-induced JAK2/STAT3 signaling through cleavage and activation of MK-mediated Notch signaling [54,55]. Intriguingly, the binding of estradiol (E2) to ERβ results in the activated ER-β binding to the estrogen response element within the MK promoter, thereby leading to the induction of MK transcription, which enhances the EMT [56].…”
Section: Critical Modulators Of the Jak2/stat3 Signaling Pathway In Emtmentioning
confidence: 99%
“…In cholangiocarcinoma, Notch 1-3 expression was associated with lower histological differentiation and poorer survival of patients, and combining gemcitabine and GSI-IX prevented gemcitabine-induced enrichment of CSClike population in in vitro models [584]. Similar to what was described in pancreatic cancer, Midkine-mediated upregulation of Notch1, responsible for Notch2 upregulation, was also reported as a resistance mechanism for biliary tract cancer [585]. In NSCLC, chronic exposure to gemcitabine drastically upregulates Notch3 expression by tumor cells, whereas the addition of DAPT sensitized cell lines to the pyrimidine analogue, affecting pro-and anti-apoptotic protein expression patterns [586].…”
Section: Gemcitabinementioning
confidence: 60%
“…AS a heparin-binding growth factor, MDK is abnormally high expressed in a variety of human malignancies and serves as an intermediary agent for the acquiring critical features of cancer, such as proliferation, metastasis, chemoresistance, migration, and angiogenesis [35][36][37][38]. Some studies have shown that MDK can be served to monitor the response to tumor treatment, while the secretion and overexpression of MDK in chemoresistant cells can protect themselves from cannabinoid and doxorubicin treatment [39][40][41][42]. Our findings uncovered that miR-1275-reduced chemoresistance was induced by the increase of MDK-mediated population of CSCs and PI3K/AKT phosphorylation and thus restored sensitivity of cells to epirubicin.…”
Section: Discussionmentioning
confidence: 99%